Gender-based violence against women users of public transport in Saltillo, Coahuila, Mexico. Issue 2 (17th February 2022) - Infante-Vargas, Diana; Boyer, Kate
ABSTRACT: This paper details the pervasiveness of gender-based violence (GBV) that women in Saltillo, Mexico experience when using public transport. Using a mixed-method approach that included a survey (N = 611) and interviews (N = 11) with transit users and a local women's rights activist, we explore the experiences of violence that women face as an everyday reality, together with issue of re-victimization, and the psychological effects that violent episodes can have on women who experience them. Adding to existing knowledge about GBV in spaces of transport, we argue that women can experience myriad wide-reaching effects beyond the event itself that include not only limits on their mobility, but also financial and emotional repercussions. Policy change is urgently needed in order to redress this problem.